2022
DOI: 10.3389/fendo.2022.907984
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Attenuates Obesity-Related Kidney Dysfunction and NLRP3 Inflammasome Activity Through the HO-1–Adiponectin Axis

Abstract: Empagliflozin (EMPA) is a novel sodium-glucose cotransporter 2 inhibitor (SGLT2i) that produces protective cardiovascular-renal outcomes in patients with diabetes. However, the effects of EMPA on obesity-related kidney disease have not been determined. The heme oxygenase-1 (HO-1)–adiponectin axis is an essential antioxidant system with anti-apoptotic and anti-inflammatory properties. This study explored whether EMPA improves obesity-related kidney disease through regulation of the renal HO-1-mediated adiponect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…It has been demonstrated in multiple animal experiments that SGLT2i can improve the terminal outcome of the kidney by promoting autophagy or improving related inflammation [ 22 , 23 ]. Similar effects on improving the inflammatory response were observed in models of infectious kidney injury and oxidative damage [ 24 , 25 ], which might be achieved by reducing the activity of NLRP3 inflammasomes [ 26 , 27 ]. In addition, autophagy may be improved through the mTOR1-related signaling pathway [ 28 ].…”
Section: Sglt2i Provide Renal Protection In Animal Modelsmentioning
confidence: 72%
“…It has been demonstrated in multiple animal experiments that SGLT2i can improve the terminal outcome of the kidney by promoting autophagy or improving related inflammation [ 22 , 23 ]. Similar effects on improving the inflammatory response were observed in models of infectious kidney injury and oxidative damage [ 24 , 25 ], which might be achieved by reducing the activity of NLRP3 inflammasomes [ 26 , 27 ]. In addition, autophagy may be improved through the mTOR1-related signaling pathway [ 28 ].…”
Section: Sglt2i Provide Renal Protection In Animal Modelsmentioning
confidence: 72%
“…Consistent with our previous study, the HFD-induced metabolic disturbance was improved by EMPA treatment (p < 0.05). 18 , 20
Figure 1 Mouse biochemistry parameters (A–J) (A) body weight, (B) fat mass, (C) fat/body weight, (D) serum triglyceride, (E) fasting glucose, (F) fasting insulin, (G) homeostatic model assessment of insulin resistance (HOMA-IR) index, (H) free fatty acids (FFA), (I) oral glucose tolerance test (OGTT), and (J) insulin tolerance test (ITT) curve. ∗p < 0.05, ∗∗p < 0.01, for (E) and (F), ∗HFD vs. CT p < 0.05, # EMPA vs. HFD, n = 5–6.
…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that EMPA can protect against obesity-related cardiac dysfunction, nonalcoholic fatty liver disease, and chronic kidney disease via different mechanisms. 18 , 19 , 20 This protection was associated with improving metabolic disruption, including a reduced fat/body weight ratio and restored glucose homeostasis. Our study further confirmed that EMPA can reduce the fat/body weight ratio and alleviate impaired glucose/insulin tolerance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regulatory effects of SGLT-2i have been implicated in ER and oxidative stress, autophagy, apoptosis, and inflammation [ 96 ]. Ye, T. et al treated HFD-fed C57BL/6J mice with empagliflozin and found that empagliflozin reduced fat mass, body weight, plasma TG and FFA levels, fasting glucose levels, and NLRP3 inflammasome activity, and induced HO-1-adiponectin-dependent signaling pathway [ 97 ].…”
Section: Autophagy In Mafldmentioning
confidence: 99%